2014
DOI: 10.1186/1748-717x-9-105
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for survival and radiation necrosis after stereotactic radiosurgery alone or in combination with whole brain radiation therapy for 1–3 cerebral metastases

Abstract: BackgroundIn the present study factors affecting survival and toxicity in cerebral metastasized patients treated with stereotactic radiosurgery (SRS) were analyzed with special focus on radiation necrosis.Patients and methods340 patients with 1–3 cerebral metastases having been treated with SRS were retrospectively analyzed. Radiation necrosis was diagnosed by MRI und PET imaging. Univariate and multivariate analysis using a Cox proportional hazards regression model and log-rank test were performed to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 27 publications
4
44
0
Order By: Relevance
“…As in previous reports (16), we found metachronous metastatic disease is one important risk factor for BM, however, despite the long survival until development of BM, survival after diagnosis of BM was only a median of 2.9 months (17,18). Our data also shows lung metastases and rectal cancer were associated with BM, and the location of the primary tumor may have a close relationship with the target organ of metastasis (2,19). These can be explained in part by the vascular anatomy of the colon and rectum.…”
Section: Discussionsupporting
confidence: 85%
“…As in previous reports (16), we found metachronous metastatic disease is one important risk factor for BM, however, despite the long survival until development of BM, survival after diagnosis of BM was only a median of 2.9 months (17,18). Our data also shows lung metastases and rectal cancer were associated with BM, and the location of the primary tumor may have a close relationship with the target organ of metastasis (2,19). These can be explained in part by the vascular anatomy of the colon and rectum.…”
Section: Discussionsupporting
confidence: 85%
“…These studies were not designed to robustly evaluate for the development of symptomatic radionecrosis and did not record asymptomatic treatment change. Multiple retrospective studies have reported higher rates of radionecrosis, ranging from 6.2 % to more than 30 % [37], likely reflecting differences in patient population, extent of follow up, and definition of radionecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastasis (BM) is the most common brain tumor leading to significant morbidity and mortality in patients with systemic malignancies. The median overall survival in patients with BM ranges between 5.7 and 15.2 months, based on the intervention . BM affects up to 40% of patients with a range of systemic malignancies and an incidence ranging between 8.3 and 14.3/100,000 populations based on epidemiological studies .…”
Section: Introductionmentioning
confidence: 99%
“…The median overall survival in patients with BM ranges between 5.7 and 15.2 months, based on the intervention . BM affects up to 40% of patients with a range of systemic malignancies and an incidence ranging between 8.3 and 14.3/100,000 populations based on epidemiological studies . With the increase in the incidence of systemic malignancies coupled with advances in systemic treatment regimens, BMs pose significant challenges to physicians managing these patients.…”
Section: Introductionmentioning
confidence: 99%